Iranian Millenarianism and Democratic Thought in the 19th Century - Cole, Juan (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2002)
This article examines the relations between the establishment of the Baha'i religion during the second half of the nineteenth century and liberaldemocratic ideas, which circulated among reformist groups in Iran during the same period. It argues that Bahã-A'llah (1817-1892), who established the Baha'i religion, was an enthusiastic supporter of representative government and constitutional monarchy. Furthermore, in his numerous writings he promoted these ideas to his followers. Based on a close reading of texts by Bahā-A'llah, his son and heir 'Abd al-Bahã and other leading contemporary Baha'i thinkers, the author concludes that millennial aspirations for a more just and egalitarian world, as envisioned in the new Baha'i religion, urged democratization and liberalization in Qajar Iran. Even more so, the liberal-humanistic thought of Bahã-A'llah was influenced by other reformist movements such as the Young Ottomans and Egyptian activists during the Uräbī revolt. Thus, this new perspective on Bahã-A'llah's scholarship and on supporters of Baha'i religion shows that they were not conservative royalists as assumed in past research, but rather innovative reformists.